Report on capacity building on mainstreaming gender to lifeland partners - Sikira, A. (2016)
The LiFELand Project team is very grateful to the CGIAR Research Program on Water, Land and Ecosystems in the Nile and East Africa Region for the financial support which enabled undertaking the Capacity Building on Mainstreaming Gender to LiFELand Partners in the Ihemi SAGCOT Cluster. We are obligated to a number of people without whom this task would not have been possible. We would like to express our most sincere gratitude to all officials and farmers consulted for their cooperation and sharing of information. We are indebted to the Regional and Local Government Authorities for their cooperation and assistance with the introduction letters to the villages and for providing us some basic information and data for their districts. We thank various investors, the NGOs and various Development Partners for providing information about their activities in the Ihemi cluster. We appreciate the support from TNC Project Management in particular Mr. Felix Kamau for being such a good project leader and for the cooperation. We thank our fellow project members from CIAT and the research assistants to the project. Finally, we thank all who in one way or another assisted in making this work successful.